2003
DOI: 10.1192/apt.9.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatry and the media

Abstract: Aspects of print, broadcast, film and ‘new media’ are related to their interactions with psychiatry. Frequent representations of mental health issues are paralleled by the adoption of psychological theories into media studies. Key areas are covered where psychiatric items diverge from other medical specialities, such as the depiction of suicide, the dominance of ‘human interest’ stories and negative representation of people with mental illness. Although the language of mental disorders is important, the power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
0
14
1
1
Order By: Relevance
“…This is in contrast to other studies which showed that presentation of mental illnesses in the form of self-portraits by the affected persons resulted in their positive image accentuating their ability to overcome stigma (Byrne, 2003; Nairn & Coverdale, 2005). This is also in contrast with recommendations for responsible journalism, which suggest that articles that involve individuals with mental illness and their families should focus not only on symptoms or consequences of the illness, but also on therapy and recovery, showing a more positive picture of living with mental illness (Nairn, 1999).…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to other studies which showed that presentation of mental illnesses in the form of self-portraits by the affected persons resulted in their positive image accentuating their ability to overcome stigma (Byrne, 2003; Nairn & Coverdale, 2005). This is also in contrast with recommendations for responsible journalism, which suggest that articles that involve individuals with mental illness and their families should focus not only on symptoms or consequences of the illness, but also on therapy and recovery, showing a more positive picture of living with mental illness (Nairn, 1999).…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have shown the relevance of associating the level of the articles' stigmatisation (global impression as named in this instrument) with certain categories; such as disorder mentioned, aggression, and source of information [9,24,[43][44][45][46]. The PICMIN instrument is designed for this kind of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Soap opera storylines are arguably more predictable than other television dramas because of the pervasive reporting of plot 'spoilers' in the tabloid press and magazines. The tendency to show users of mental health services in a negative light (Byrne, 2003) makes prior awareness of dramatic content important.…”
Section: Discussionmentioning
confidence: 99%